2021
DOI: 10.1007/s12144-021-01616-8
|View full text |Cite
|
Sign up to set email alerts
|

The impact of emotional contagion on workplace safety: Investigating the roles of sleep, health, and production pressure

Abstract: Using emotional contagion theory and the Job Demands-Resources model as a theoretical foundation, we tested the proposition that higher levels of contagion of anger (i.e., a demand) vs. higher levels of contagion of joy (i.e., a resource) will be associated respectively with more vs. fewer sleep disturbances and health problems, which in turn are related to more workplace accidents and injuries. Moreover, we examined the moderating impact of production pressure (i.e., a contextual demand) on the relationship b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 63 publications
0
6
0
Order By: Relevance
“…According to the JD-R model, these adverse work environments put chronic job demands on workers, which depletes their mental and physical resources and resulting in exhaustion and health problems (Bakker & Demerouti, 2007). Indeed, recent studies have shown that high production pressure is associated with adverse safety outcomes such as less compliance with safety, poorer safety performance, greater accident underreporting, and a higher number of experienced accidents (Jiang & Probst, 2015; Longoni et al, 2013; Petitta et al, 2023; Probst & Graso, 2013).…”
Section: The Relationship Between Production Pressure and Work-relate...mentioning
confidence: 99%
See 1 more Smart Citation
“…According to the JD-R model, these adverse work environments put chronic job demands on workers, which depletes their mental and physical resources and resulting in exhaustion and health problems (Bakker & Demerouti, 2007). Indeed, recent studies have shown that high production pressure is associated with adverse safety outcomes such as less compliance with safety, poorer safety performance, greater accident underreporting, and a higher number of experienced accidents (Jiang & Probst, 2015; Longoni et al, 2013; Petitta et al, 2023; Probst & Graso, 2013).…”
Section: The Relationship Between Production Pressure and Work-relate...mentioning
confidence: 99%
“…Such a situation may trigger a synergistic depletion of cognitive resources, resulting in a significant increase in cognitive lapses and slips, and consequently, a higher number of workplace injuries. Similar studies examining the interplay between different job demands on employee strain are still exceptionally rare even though work environments are multivariate in nature, and the examination of only a direct effect of job demands may paint an overly simplistic picture of their detrimental influences (for notable exceptions, see Petitta et al, 2023;van Woerkom et al, 2016). In this study, we comport with the JD-R model to fill this gap by hypothesizing that:…”
Section: Working In a Qualitative Jic: Impacts On Cognitive Failures ...mentioning
confidence: 99%
“…For example, scholars contend that low sleep quality may harm individuals' alertness (Saper et al, 2005) and contribute to occupational injuries (Barnes and Wagner, 2009). Other negative work-related outcomes of sleep disturbance include reduced self-control and increased workplace deviance (Christian and Ellis, 2011), decreased self-efficacy (Nazari et al, 2014), and reduced well-being (Petitta et al, 2021). Prior studies have also revealed that low sleep quality has deleterious effects on individuals' thinking ability (Horne, 1988) and, specifically, on their innovative thinking capacity (Harrison and Horne, 1999).…”
Section: Moderating Role Of Sleep Qualitymentioning
confidence: 99%
“…Sufficientsleep of good quality is required for the optimal functioning of the human mind and body.For adults, the American Academy of Sleep Medicine (AASM) and Sleep Research Society (SRS) currently suggest seven or more hours of sleep per night in order to maintain good health 1,2 . Studies have shown that adequate quantity and good quality sleep are instrumental in restoring andmaintaining cognitive and psychomotor performance and mental and physical health [3][4][5][6] .There is growing interest in studying sleep disordersbecause sleepiness and fatigue are epidemics leading to various health issues 7 . Insomnia is one type of sleep disorder in which individuals struggle to fall or stay asleep even when given the chance, resulting in at least three times a week in a month of sleep deprivation.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers in Pakistan have conducted studies with similar methods, with one study reporting 650 cases in a just 9 months 4 . Most cases of peritonitis are caused by a gastrointestinal perforation or anastomotic leak 5 . In the case of peritonitis, anaerobes and gramnegative organisms are mostly responsible for sepsis and morbidity due to the overactive inflammatory cascade brought on by the release of endotoxins 5 .Clinical evidence is used to identify peritonitis.…”
Section: Introductionmentioning
confidence: 99%